Factors associated with caesarean deliveries among child-bearing women in Pakistan: secondary analysis of data from the Demographic and Health Survey, 2012-13 - Aaisha Amjad; Uzair Amjad; Rubeena Zakar; Ahmed Usman; Muhammad Zakria Zakar; Florian Fischer (BMC, 2018)
Abstract Background The increasing rate of caesarean deliveries has become a serious concern for public health experts globally. Various medical and non-medical factors, such as maternal socio-demographics, are found to be responsible for this upsurge. Like in other countries, the rate of caesarean sections has increased in Pakistan as well. Therefore, there is a need to investigate the factors behind this increase. This study aims to assess the determinants associated with caesarean deliveries among child-bearing women aged 15-49 years in Pakistan. Methods Secondary data analysis was conducted on nationally representative cross-sectional survey data from the Pakistan Demographic and Health Survey, 2012-2013. The analysis was limited to mothers aged 15-49 years, who had given birth to at least one child during the 5 years immediately preceding the survey (n = 7461). Maternal socio-demographic characteristics and pregnancy-related variables, including antenatal care utilisation, place of delivery and pregnancy complications were considered as independent variables. The association between caesarean section deliveries (outcome variable) and its determinants was assessed by calculating unadjusted and adjusted odds ratios with 95% confidence intervals using a multivariable binary logistic regression. Results Of the women who had given birth to at least one child during the previous 5 years, the percentage of mothers who delivered their babies through caesarean section was found to be 13.6%. The likelihood of caesarean deliveries was associated with mothers aged more than 24 years, women residing in Punjab province, women belonging to the richest class, women with higher education, women employed at professional/managerial/technical level, and women residing in an urban setting. Additionally, the women who had pregnancy complications, a high utilisation of antenatal care and delivered their babies in private hospitals were found to have higher chances of caesarean deliveries. Conclusions The study revealed that there are a high percentage of women delivering babies through caesarean section in Pakistan. Therefore, strict measures need to be taken to deal with this concern. For example, detailed medical justifications by doctors for performing caesarean sections and awareness among women regarding the reduction of pregnancy complications can help to reduce the chances of malpractice related to caesarean deliveries.